Legal Politics in Indonesia: Ensuring Legal Certainty and Substantive Justice within a Democratic Rule of Law - Ahmad Fadli; Muhammad Qasim Hamzah; Priyanto; Fajar Abadi Jaya Tadjuddin S (Journal AGENCY, 2026)
Legal politics constitutes a fundamental policy framework that determines the direction of lawmaking, implementation, and enforcement within a democratic rule of law. In Indonesia, achieving a balance between legal certainty and substantive justice remains a persistent challenge due to overlapping regulations, inconsistent law enforcement, and the influence of political interests on legislative processes. This study aims to analyze the role of legal politics in ensuring legal certainty and substantive justice while identifying the principal obstacles affecting its implementation in Indonesia. A normative legal research approach was employed using qualitative analysis of constitutional provisions, statutory regulations, legal doctrines, and relevant scholarly literature. The analysis demonstrates that legal politics serves as the primary instrument for aligning legislation with constitutional values embodied in Pancasila and the 1945 Constitution. Effective legal politics contributes to legal certainty by promoting coherent, transparent, and consistent legislation, while simultaneously supporting substantive justice through the protection of human rights, equal access to justice, and non-discriminatory law enforcement. Nevertheless, the findings reveal that regulatory disharmony, political intervention, institutional inconsistency, and limited public participation continue to undermine the realization of these objectives. The study concludes that strengthening legislative planning, enhancing regulatory harmonization, safeguarding judicial independence, improving law enforcement integrity, and expanding meaningful public participation are essential to developing a legal system that combines predictability with fairness. Such reforms are necessary to reinforce democratic governance, uphold the rule of law, and ensure that legal development in Indonesia remains responsive to constitutional principles and the evolving needs of society.